Perbedaan Komposisi Non Karkas Domba Ekor Gemuk yang Diberi Pakan Ampas Tahu dan Pencukuran Wol - Baihaqi, M.; Meigyantoko, D.; Rahayu, S. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2013)
The effects of wool shorn and diets on non carcass characteristics were evaluated using twelve Javanese fat-tailed male lambs with initial body weight of 17.40±1.10 kg (CV=6.3%). Animals were reared for three months of experimental period then were slaughtered to measure non carcass component. The first treatment was different of diets (P1= grass + concentrates and P2= grass + concentrates + soybean tofu waste) and the second treatment was wool shearing (C1= unshorn sheep and C2= shorn sheep). Data of non carcass was analyzed by Analysis of Covariance (ANCOVA) with slaughter weight as covariable. The result showed that treatments did not significantly influence (P>0.05) on weight and percentage of all noncarcass component.But interactions between treatment has significantly influence (P<0.01) on weight and percentage of reproduction tract. FT thatgiven by soybean tofu waste that shorn and not shorn, without given by soybean tofu waste that shorn and unshorn resulted percentage of non-carcass 53.06, 52.52, 56.98, and 57.62% of slaughter weight, respectively.